Benign Lymphoid Hyperplasia of the Tongue Base Causing Upper Airway Obstruction - Sands, Noah B.; Tewfik, Marc (Case Reports in Otolaryngology, 2011)
Severe benign lymphoid hyperplasia (LH) is unusual in the head and neck region, but the diagnosis of LH is of clinical importance as it may be confused with malignant lymphoma, both on clinical examination and pathologically. While the etiology is poorly understood, a number of previous theories exist, which are included here in the context of a literature review. In this paper we present a case of severe pharyngeal lymphoid hyperplasia causing airway obstruction and requiring tracheotomy and subsequent surgical debulking.